Strategi Komunikasi Kelompok Komunitas Vespa Orijingan dalam Melestarikan Terumbu Karang di Gili Trawangan Lombok - Ayu Savitri; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
he destruction of coral reefs in Gili Trawangan Lombok does not prevent the preservation of nature for the creatures that live in the seas of Gili Trawangan Lombok. The purpose of this study was to find out the strategies carried out by the Vespa Orijingan community in conserving coral reefs in Gili Trawangan Lombok. The strategy for conserving coral reefs is in accordance with the “P” theory of the process carried out by this community. This type of research is qualitative and descriptive analysis with the case study method of Robert K. Yin. The paradigm in this study uses post-positivism. In this study using the theory of planning and communication strategies from Hafied Cangara so that in theory it gives the result that this community has a strategy in the "P" process where activities are carried out in a unique way and uploaded on Instagram social media.